An Approach for the Hematologic Challenges of Helicobacter pylori in Children: An Expensive Cost of Parents’ Misbehavior towards their Kids - Nasrat, Abdullah M.; Ashour, Rania (Medical Science: Trends and Innovations Vol. 4, 2025)
The challenges constituted by H. pylori management would render any simple strategy that proves to be safe and effective in dealing with H. pylori eradication greatly welcomed particularly in those hematologically compromised children. The mucosal lymphocytic response to H. pylori significantly increases the risk of gastric MALT lymphoma as the vast majority of gastric MALT lymphoma patients are affected with H. pylori. Interestingly; both H. pylori and MALT lymphoma are so linked as if they were almost born simultaneously. The vinegar therapy is applicable in different regimens for the eradication of H. pylori among children with hematologic disorders. As the vinegar increases the absorption of non-meat iron which is not desirable in thalassemia patients; therefore, vinegar therapy should be given away from the meals in those patients. Fortunately, the ideal vinegar regimen is to get the vinegar mixed with yoghurt, which is convenient in thalassemia as the yoghurt helps to decrease non-meat iron absorption.